Impact of technology on upgrading slums and the moderating role of upstream influences: a contemporary approach to urban planning - Khan, Muhammad; Bilal, Komal; Alam, Gohar (Frontiers in Built Environment, 2024)
The study aimed to determine the effect of technology on the up gradation of slums in Islamabad along with the moderating role of upstream influences between them. In this concern, the researcher used a quantitative research design and to accumulate the data, a close-ended survey questionnaire was opted. The sample size considered in this research was 293 participants sbelonging to the urban planning of Islamabad. To evaluate the data and hypothesised model, Structural Equation Modelling (SEM) was used. ssIt was also revealed that upward influences moderated the association between technology and slum upgradation significantly, particularly regarding governance, religion, and gender roles. However, this research is limited to Islamabad only, therefore, the implications of this study cannot be generalized. Consequently, it has been recommended that upward influences based on crime and mafia along with governance should be controlled to upgrade Islamabad based slums.